Digestão anaeróbia de resíduos de restaurantes: partida do reator e avaliação do biofertilizante - Velho, Douglas Ferreira (Universidade do Vale do Rio dos Sinos, 2016)
The increase in the generation of municipal solid waste, together with the inadequate forms of treatment and disposal contribute directly and significantly to the environmental problems. In this scenario, it is necessary to develop alternatives to other benefits in addition to the appropriate disposal. Anaerobic digestion is a viable alternative and economically interesting for the treatment of the organic fraction of municipal solid waste. Whereas in our country the organic fraction is predominant in urban solid waste, corresponding to an average of over 40% in the composition, at the same time reducing the volume of waste sent to landfills, the process generates products such as biogas and biofertilizers for agricultural use. This research aimed to evaluate the treatability of the organic fraction of household waste from the preparation and after consumption of meals from a university restaurant in a reactor operated by batch and qualify the characteristics of the generated biofertilizers. To achieve this goal, the research was conducted in three phases, with the initial phase were held four batches were analyzed in which the proportions of the waste and inoculum for starting the reactor without acidification occurred. The second stage consisted of six batches, which were monitored in the main operating parameters and the third stage where we evaluated the chemical, physical and microbiological biofertilizer generated at the end of the second stage trials. The first step results indicated that the ratio of 6: 1 in terms of total volatile solids, and sludge from a UASB reactor and solid waste putrescible respectively, showed a suitable starting system without occur acidification to pH between 6.9 and 7.7. In the second stage, the monitoring of key operating parameters allowed during the experiment the proportion in terms STV be reduced, reaching 1: 1 inoculum and substrate respectively in the batch 10, thus allowing treatment of a larger quantity of waste compared to the initial test. The results showed that monitoring the pH was maintained within the range considered optimal between 6.0 and 8.0, but the period twenty-two days adopted as the retention time was insufficient to degradation and subsequent removal of matter organic, and only the batch 10 was effective in removing STV 8.1% and 33.5% total organic carbon. Physical analysis of biofertilizers generated at the end of each test pointed humidity above those permitted by law and is intended only for use via spraying. Chemically biofertilizer showed nitrogen deficiency, evidenced in the high ratios C: Initial N and obtained final and lack of nutrients such as phosphorus whose results were below 1% minimum required by the legislation and potassium, an element that was not detected in the equipment used. The sanitary quality of the compound met the legislation for the presence of viable helminth eggs, and all tests showed lower results to a unit / 4G, but showed results above the limit for fecal coliforms. The germination test confirmed the absence of phytotoxicity of products.
Keywords: Digestão anaeróbia; Biodigestor; Biofertilizante; Anaerobic digestion; Digester; Bio-fertilizer; ACCNPQ::Engenharias::Engenharia Civil